Symptom Palliation in Patients with Bone Metastases Treated with Radiotherapy - Rastogi, Kartick; Gupta, Shivani; Bhaskar, Sandeep; Bhatnagar, Aseem-Rai; Bairwa, Subhash-Chand; Jain, Sandeep (Indian Journal of Medical and Paediatric Oncology, 2019)
Context: Skeleton is the most common organ affected by metastases. Bone pain is the most common symptom of metastatic bone disease. The treatment of bone metastasis is primarily palliative requiring multidisciplinary therapies; radiotherapy (RT), however, remains the cornerstone of the treatment. Aims: The aim of this study is to measure the effectiveness of RT in terms of symptomatic relief in pain and insomnia, improvement in stability/movement, and decrease in the requirement of analgesics by patients using the Hundred Paisa Pain Scale. Subjects and Methods: The RT records of 226 patients with bone metastasis treated at the department of Radiotherapy, SMS Medical College, Jaipur; from July 2015 to December 2016 over cobalt-60 teletherapy unit were analyzed. The RT dose fractionation ranged from 30 Gy in 10 daily fractions, 20 Gy in 5 daily fractions, 12.5 Gy in 2 weekly fractions, and 8 Gy in single fraction. Results: The median age of the cohort was 54 (range, 29–84) years. The most common site of primary tumor was lung (30.1%), followed by breast (12.4%) and prostate (11.9%). The most common bone involved was vertebrae (71.2%), followed by pelvis (14.6%); among vertebrae, thoracic vertebrae were most commonly involved (63.9%), followed by lumbar vertebrae (57.8%). The maximum relief in pain was seen with 6.25 Gy/fraction schedule, whereas the maximum improvement in stability/movement was noted with 3 Gy/fraction schedule. The 8 Gy single-fraction schedule was associated with maximum relief in insomnia and decrease in analgesic requirement. Conclusion: The current institutional protocol of weekly hypofractionated palliative RT of 6.25 Gy per fraction up to a maximum of four fractions given on Saturday has shown results comparable with other schedules with well tolerance and achievement of acceptable symptom palliation. This weekly schedule is practically convenient to both the patients who mostly came from far-flung areas and the institute as it spares the already overburdened machine to carry on conventional RT from Monday to Friday.
Keywords: Bone metastases; palliation; radiotherapy